Meningkatkan Hasil Belajar Melalui Canva pada Materi Bersikap Kritis dan Bertanggungjawab Terhadap Media Massa dengan Model Problem Based Learning di Kelas X SMA Negeri 2 Temanggung - Agustina Puji Astuti; Nerita Setiyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning is a process of implementing actions that involve interactions between teachers and students, along with reciprocal communication that occurs in the context of education to achieve learning goals. Manifested in government regulations, namely Government Regulation Number 57 of 2021 concerning National Education Standards which was amended by Government Regulation No. 4 of 2022, it is stated that process standards are minimum guidelines in implementing the education system in all regions subject to the laws of the Unitary State of the Republic of Indonesia. This is also reinforced by Permendikbud Ristek No. 16 of 2022 in Chapter I article 1 which discusses process standards. The article describes process standards referring to the minimum criteria of the learning process that apply to various paths, levels of education, and types with the aim of achieving graduate competency standards. The objectives of the study include (1) to determine how the implementation of the Problem Based Learning model improves student learning outcomes with the help of Canva on the material of being critical and responsible towards mass media in class X of SMA Negeri 2 Temanggung, (2) to determine the application of the use of Canva in exploring the learning outcomes of class X students of SMA Negeri 2 Temanggung on the material of being critical and responsible towards mass media. The type of research used is qualitative with a descriptive approach. Data collection techniques in this study used observation and tests. The data analysis techniques used consisted of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the formulation of the problem. The use of the Problem Based Learning model according to the syntax which includes student orientation to the problem, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem-solving process, is effective in helping to improve learning outcomes and critical reasoning of students on the material of being critical and responsible towards mass media.